2020
DOI: 10.37819/biosis.001.01.0049
|View full text |Cite
|
Sign up to set email alerts
|

A New Genus of Crickets (Orthoptera: Gryllidae) in Mid-Cretaceous Myanmar Amber

Abstract: Crickets (Orthoptera: Grylloidea) are a highly diverse and successful group that due to their chirping are often heard more often than they are seen. Their omnivorous diet allows them to exist in a variety of terrestrial habitats around the world. In some environments, cricket populations can build up and become plagues, resulting in significant damage to seedling crops. A new genus and species of cricket, Pherodactylus micromorphus gen. et sp. nov. (Orthoptera: Gryllidae) is described from mid-Cretaceous Myan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…In fact, Pherodactylus certainly belongs to the Gryllidae family, as shown by the three apical spurs on fore tibia, with however a unique specialization (spurs all on inner side of tibia). The lack of setae on head dorsum (apomorphy) and of subapical spurs on hind tibia (apomorphy) are considered characters of the subfamily Gryllinae: they allow the assignment of the remarkable fossil of Pherodactylus micromorphus in this subfamily, as proposed by Poinar et al (2020), but using a different set of characters.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Pherodactylus certainly belongs to the Gryllidae family, as shown by the three apical spurs on fore tibia, with however a unique specialization (spurs all on inner side of tibia). The lack of setae on head dorsum (apomorphy) and of subapical spurs on hind tibia (apomorphy) are considered characters of the subfamily Gryllinae: they allow the assignment of the remarkable fossil of Pherodactylus micromorphus in this subfamily, as proposed by Poinar et al (2020), but using a different set of characters.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is hard to observe the structures associated with climbing on the plants from these ambers, their slender thorax legs suggest that they were most likely adapted to live in vegetation close to the ground rather than to be ground-dwellers. It has already been found that Elcanidae, Trigonidiidae, Gryllidae, Mogoplistidae, Gryllotalpidae, and Tridactyllidae, in the northern Myanmar ambers [ 19 , 20 , 21 , 22 , 29 , 30 ], reflect a broad adaption of the ecological niche of orthopterans in the Myanmar amber biota.…”
Section: Discussionmentioning
confidence: 99%
“…The insects discovered from the northern Myanmar ambers are quite diverse. To date, four Grylloidea species, Protomogoplistes asquamosus Gorochov, 2010 (Mogoplistidae); Pherodactylus micromorphus Poinar, Su and Brown, 2020 (Gryllidae); Birmaninemobius hirsutus, Xu, Zhang, Jarzembowski, and Fang, 2020; and Curvospurus huzhengkun, He, 2022 (Trigonidiidae), have been described [ 6 , 20 , 21 , 22 ]. Here, we describe two new genera with two new species of Oecanthinae of Gryllidae from the mid-Cretaceous from the Hukawng Valley of Kachin Province in northern Myanmar.…”
Section: Introductionmentioning
confidence: 99%
“…Besides this, a further interpretation of the enclosed nymphs remains rather speculative. However, based on tarsal morphology and number of elements (less than four), a shorter tibia than femur at the hindleg (Poinar et al 2020 and references therein) and general habitus, an ingroup position within Gryllidae seems plausible. Grimaldi et al (2002) reported eight specimens (six of the group Grylloidea), two nymphs putatively of the group Grylloidea have been depicted.…”
mentioning
confidence: 99%
“…Grimaldi et al (2002) reported eight specimens (six of the group Grylloidea), two nymphs putatively of the group Grylloidea have been depicted. Recently, a late instar of a female specimen of Gryllidae (Poinar et al 2020) was described (Pherodactylus micromorphus Poinar Jr., Su & Brown, 2020). The here described orthopteran nymphs (BUB 3193) cannot be conclusively interpreted as representatives of any formally described species (or genus) in Myanmar amber, as they differ significantly in morphology, or the known specimens represent adults or late immature stages.…”
mentioning
confidence: 99%